Sozio-Design : relevante Projekte : entworeen für die Gesellschaft = Socio-design : relevant projects : designed for society - Stocker, Karl, 1956- (Birkhäuser Verlag, 2017)
"On the occasion of Graz UNESCO City of Design, the Joanneum University organizes an annual lecture series with high-profile speakers. It focuses on different aspects of the international discourse on design. For the first time, a symposium has been organized as part of this event. The presentations provide the material for the Socio-Design book. While the gleaming aesthetics of commercial goods conspire to form a modern 'ego image', there is - beyond the pressure to consume - a development that focuses on the social relevance of design relating to cultural objects: in these times of social change, Socio Design is increasingly garnering attention. The book documents six design contributions which have a stabilizing and balancing effect owing to a new arrangement of social interactions."--Provided by publisher